Teori Penjulukan - Ahmadi, Dadi (Mediator, 2005)
Labelling theory, famously associated with Howard Becker, was resulted from deviation studies which flourished in the late years of 1950s. Labelling theory, as part of interaction symbolic school of thought, assumed deviation as interactional function between deviants and non-deviants, rather than individual inherent characteristic. Labelling theory consisted of four tenets: (1) Social label for particular action; (2) criminal act is resulted from social rules; (2) social control is worsening criminal problems; and (4) there are interrelated bonds within people who being labeled and their counterparts who give them any label. Media, for some ideological reasons, implied labeling theory in their narration which acted as a mean for social construction.